Unique photothermal material: Copper phosphate (Cu3P2O8) with broadband visible-to-near-infrared absorption properties for efficient solar steam generation - Shridharan, Tatachari Santhanagopalan; Lee, Jong Ho; Tan, Runfa; Sivanantham, Arumugam; Han, Hyun Soo; Jung, Hyun Suk; Cho, In Sun (Desalination, 2024)
Effective harnessing of renewable solar energy in interfacial solar steam generation (ISSG) is a promising solution for addressing freshwater scarcity worldwide. Therefore, the development of photothermal materials plays a pivotal role in achieving efficient ISSG performance. This paper reports on an innovative photothermal material, copper phosphate (Cu3P2O8; CuPO), with broadband visible-to-near-infrared (Vis-to-NIR) absorption for ISSG. CuPO exhibited favorable characteristics, including extensive light absorption across the Vis to NIR spectrum (500–2200 nm), low thermal conductivity (0.64 W/m·K), high photon-to-heat conversion efficiency (87.9 %), and inherent hydrophilicity. When subjected to simulated sunlight (AM1.5G, 100 mW/cm2), the CuPO-coated polyurethane membrane demonstrated remarkable water evaporation performance (2.05 kg/m2·h) and ISSG efficiency (95.0 %). Notably, employing an ultraviolet cutoff filter (< 450 nm) revealed a substantial NIR absorption contribution of CuPO, surpassing 80 % of its overall performance. Moreover, the CuPO photothermal membrane exhibited durable ISSG performance over 25 cycles, underscoring the structural robustness and resilience of CuPO. Our findings offer a promising foundation for designing cost-effective, high-performance ISSG systems utilizing copper-based complex oxides.
Keywords: Broadband light; Broadband light absorption; Interfacial solar steam generation; Low thermal conductivity; Near Infrared; Near-infrared; Solar steam; Steam generation; Triclinic structures; Visible-to-near-infrared; Broadband light absorption; Copper phosphate; Interfacial solar steam generation; Low thermal conductivity; Triclinic structure; Vis-to-NIR